Knowledge and attitudes towards the use of skin care-whitening products among students at MAN Temanggung - Khasanah, Amalia; Yuliastuti, Fitriana (Borobudur Pharmacy Review, 2026)
Skin beauty is one of the factors influencing adolescents’ appearance and self-confidence, leading to a growing interest in using whitening skin care products. However, insufficient knowledge and lack of selective attitudes in choosing products can pose health risks due to harmful ingredients such as hydroquinone and mercury. This study aims to analyze the knowledge and attitudes of MAN Temanggung students regarding the use of whitening skin care products. A quantitative descriptive research method was employed with a population of 743 students, and a sample of 137 respondents was selected using probability sampling. Data were collected via a Google Form questionnaire, measuring knowledge with a Guttman scale and attitudes with a Likert scale. The results showed that the majority of students had good knowledge (84%) concerning product legality, benefits, side effects, ingredients, and storage. Meanwhile, students’ attitudes toward using whitening skin care were mostly categorized as good (65%), although there was still a tendency to choose products based on advertisements or the results observed on others’ skin. These findings highlight the need for further education to improve adolescents’ awareness in selecting safe and suitable products according to their skin conditions.